The effect of two point mutations in GDF-5 on ectopic bone formation in a β-tricalciumphosphate scaffold - Kasten, Philip; Beyen, Ingo; Bormann, Dirk; Luginbühl, Reto; Plöger, Frank; Richter, Wiltrud (Biomaterials, 2010)
The osteoinductivity of human growth-and-differentiation factor-5 (GDF-5) is well established, but a reduced amount of ectopic bone is formed compared to other members of the bone morphogenetic protein (BMP) family like BMP-2. We hypothesized that swap of two BMP-receptor-interacting residues of GDF-5 to amino acids present in BMP-2 (methionine to valine at the sites 453 and 456) may improve the bone formation capacity of the mutant GDF-5. Heterotopic bone formation of a mutant GDF-5 coated β-TCP carrier was compared to carriers coated with similar amounts (10 μg) of GDF-5 and BMP-2 in SCID mice. Four week explants revealed 6-fold higher ALP activity in the mutant GDF-5 versus the wild type GDF-5 group (p < 0.0001) and 1.4-fold higher levels compared to BMP-2 (p < 0.006). Bone area in histology was significantly higher in mutant GDF-5 versus all other groups at 4 weeks; however, at 8 weeks BMP-2 reached a similar neo-bone formation like mutant GDF-5. Micro-CT evaluation confirmed higher values in the mutant GDF-5 and BMP-2 groups compared to wild type GDF-5. In conclusion, the mutant GDF-5 showed superior bone formation capacity than GDF-5, and a faster induction at similar final outcome as BMP-2. Mutant GDF-5 thus represents a promising new GDF-5 variant for bone regeneration possibly acting via an increased binding affinity to the BMP-type I receptor.